Findings of a study of pigment epithelium-derived factor (PEDF) levels in vitreous samples from patients with proliferative diabetic retinopathy - A.A. Putienko; Elhage Emhamed Ali Abdalslam Emhamed (Ukrainian Society of Ophthalmologists, 2016)
Purpose: To investigate the relationship, if any, between vitreous pigment epithelium-derived factor (PEDF) levels and a number of clinical factors used to assess the functional activity of the retina after an intravitreal surgery for complications of proliferative diabetic retinopathy (PDR). Materials and Methods: Seventy PDR patients (70 eyes) were involved into the study. PEDF levels in vitreous samples were quantified by enzyme-linked immunosorbent assay. Results: In vitreous samples from eyes with PDR the mean ± SD PEDF level was 3.26 ng/mL ± 1.57 ng/mL. Vitreous PEDF levels were statistically significantly higher for eyes operated on for vitreous hemorrhage (VH) only than for eyes operated on for VH in the presence of macular traction detachment (t=2.35, р=0.022). The lower was the vitreous PEDF level (lower median value, 3.12 ng/mL), the more severe was retinal ischemia, which was confirmed by electrophysiological examination (namely, the parameters of the oscillatory potentials). It was found that when the level of PEDF in the vitreous is decreased, retinal neurodegeneration develops, with the greatest damage exhibited by bipolar, amacrine, and Muller cells. Conclusions: Parameters of photopic and 30 Hz flicker ERG as well as of oscillatory potentials are surrogate indicators of levels of PEDF in ocular tissues, and may be used in later studies for investigation of the role of PEDF levels in pathological processes in the eye.